GLUTATHIONE TRANSFERASE GENE POLYMORPHISM IN END STAGE RENAL DISEASE - Šuvakov, Sonja R.; Simić, Tatjana; Damjanović, Tatjana (Medicinski podmladak, 2016)
Chronic kidney disease is described as a progressive and irreversible deterioration in kidney function. When there is less than 10% of nephron function pertained, patients face end-stage renal disease, where renal replacement therapy is needed. Data show that the most common method used to treat advanced and permanent kidney failure is hemodialysis. . Increased oxidative stress is a hallmark of end-stage renal disease (ESRD). Glutathione S-transferases (GST) are involved in the detoxification of xenobiotics and protection of oxidative damage. The role of genetic polymorphism of antioxidant enzymes GSTA1, GSTM1, GSTP1 and GSTT1 in susceptibility towards end-stage renal disease development has become prominent recently. Furthermore, GST gene polymorphism may modulate the degree of oxidative stress byproducts in end-stage renal disease patients and, therefore, influence their overall and cause-specific cardiovascular mortality.